A case of catecholamine-induced cardiomyopathy treated with extracorporeal membrane oxygenation. Issue 9 (30th September 2019) - Garla, Vishnu Vardhan; Gosi, Shiva; Kanduri, Swetha; Lien, Lillian
Abstract : A 55-year-old female patient was presented with severe dyspnea due to sudden onset of heart failure (ejection fraction (EF) <10%). Echocardiogram showed a takotsubo pattern with an akinetic apical segment. Coronary angiography did not reveal any obstructive disease. She became hypotensive which was refractory to conventional pressor agents. Catecholamine-induced cardiomyopathy was suspected after the CT scan of the abdomen showed a 4 cm necrotic right adrenal mass consistent with pheochromocytoma (PHEO). Venous arterial extracorporeal membrane oxygenation and α blockers were initiated. There was a rapid improvement in cardiac function with EF normalising in 1 week. Subsequently, β-blockers were added and right adrenalectomy was done 3 weeks after the admission. She did extremely well after surgery with her blood pressure normalising without the need for antihypertensive therapy. Genetic evaluation revealed no pathogenic mutations implicated in the development of PHEO.